Behind Enemy Lines : The Defeat of Isis, the Fall of the Kurds, the Conflict with Iran - Cockburn, Patrick (London Verso, 2021)
"The war of truth and lies in the Middle East. In this urgent and timely book, Patrick Cockburn writes as a historian of the present to describe the "forever wars" in the Middle East. Donald Trump promised to end these conflicts but failed. Now it is President Biden's turn to decide whether the United States can back away from the most violent and unstable region in the world. The US and its allies do not have the strength to win, but they do have the power to avoid defeat, protracting conflicts interminably in the process. So far, there is little to suggest Biden will escape the regional quagmire that trapped his predecessors. In Behind Enemy Lies, Cockburn examines the causes of these endless wars and why reporting on them in the West has markedly deteriorated in recent years. Governments and the public know less and less about who is fighting and why; propaganda increasingly replaces well-informed reporting. The modern era in the Middle East is notable not only for failed states but for failed journalism."--Publisher's website
Keywords: Middle East -- Politics and government -- Iran -- Foreign relations -- 21st century